(untitled) (Teaching and Learning Inquiry, 2017)
Scholarly personal narrative (SPN) extends the available methodologies by which researchers conduct the Scholarship of Teaching and Learning (SoTL). In this article, the authors define SPN, which interprets personal experience through scholarly frameworks, leveraging the power of reflective practice to understand the interpersonal dynamics of both the classroom and wider academic communities. SPN fosters disciplinary understandings of SoTL and bridges discourse barriers in order to illuminate the complex environments of teaching and learning. The article examines how widely-accepted definitions of scholarship apply to SPN and provides a scholarly approach for researchers to analyze personal experience as a pool of data, employ a range of analytical techniques, and identify significant results. Through an analysis of two articles, the authors discuss the usefulness of SPN both as a major and minor critical lens. The inclusion of SPN may enrich SoTL pluralism and contribute to the knowledge of the complex contexts and influences that shape instructors, learning environments, and student experiences.